The financial and non‑financial performance indicators in strategic reports of companies from the UK – relevance from the perspective of socially responsible investors - Michalak, Jan (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The article aims to investigate which performance indicators are revealed in strategic reports of companies listed on the London Stock Exchange whether they can constitute relevant source of information to evaluate companies for investors using socially responsible investment strategies. The research method used in the article is content analysis of 60 reports of companies included in the FTSE techMARK. The research results indicate that the strategic report is a potentially relevant source of information for investors using ESG integration and commitment strategies, that dominate in the UK. Non‑financial KPI, disclosed in strategic reports, are often leading indicators and may facilitate the preparation of forecasts of future profits and cash flows of companies by investors. They also help in the creation and adjustments of investment portfolios by investors using socially responsible investment strategies. Usefulness of strategic reports for socially responsible investors is, however, limited by different format of the presented data and the relatively high variety of indicators, that makes them difficult to compare.